Kadar Fibrinogen Plasma sebagai Faktor Prognostik Karsinoma Hepatoseluler: Analisis - Sidik, Abdul Jafar; Ridayanto, Wandy (PT Kalbe Farma Tbk., 2025)
Introduction: This article aims to determine the role of plasma fibrinogen level as a prognostic factor for hepatocellular carcinoma patients. Method: A structured literature review will be conducted through PubMed, Google Scholar, and ScienceDirect, according to the selected clinical questions. Literature selection was based on inclusion and exclusion criteria. The three selected literature were then critically appraised using criteria that included validity, importance, and applicability. Discussion: The three kinds of literature in this article all state that high plasma fibrinogen levels correlate with poor overall survival in hepatocellular carcinoma patients. Conclusion: Plasma fibrinogen levels may act as a prognostic factor for overall survival in hepatocellular carcinoma patients.